An appraisal on the administration of fatwa in Malaysia - Ibrahim, Badruddin; Mohd, Azizah; Abdul Rashid, Siti Zainab (American Scientific Publishers, 2016)
The outstanding ability of islamic law to respond to changes and development has been accomplished through the institution of fatwa. Due to the multiplicity of ethnics and culture in Malaysia, the role of this institution became imperative with regards to the rapid changes and progress by means of globalisation. Therefore,, fatwa has been institutionalised and utilised in all aspects of administration and activities, This comes into existence by way of codified law concerning the administration of Islamic Religious Affairs, especially the fatwa institution. This article aims to highlight the administration of fatwa in Malaysia well as the challenge towards fatwa's unification. For this purpose, the law and regulations that govern the fatwa, as well as the institution as the main authority in fatwa in issuance will be highlighted. This covers the administration of fatwa at the state and national level. Several fatwa will be cited for illustrative purposes of the necessity of fatwa standardisation, in addition to the improvement of the fatwa institution. This article also suggests several solutions to enhance the formulation of fatwa which hopefully minimise the conflict amongst the fatwas and avoid the confusion in the midst of the people of the community.